The evolution of humanitarian mapping within the OpenStreetMap community - Herfort, Benjamin; Lautenbach, Sven; Albuquerque, João Porto de; Anderson, Jennings; Zipf, Alexander (Scientific reports, 2021)
In the past 10 years, the collaborative maps of OpenStreetMap (OSM) have been used to support humanitarian efforts around the world as well as to fill important data gaps for implementing major development frameworks such as the Sustainable Development Goals. This paper provides a comprehensive assessment of the evolution of humanitarian mapping within the OSM community, seeking to understand the spatial and temporal footprint of these large-scale mapping efforts.
Gesehen am 19.02.2021